Rhythm & clues [large type] - Jaffarian, Sue Ann, 1952- (Jaffarian, Sue Ann, 1952- Odelia Grey mystery., 2017)
It's a rockin' flashback for Odelia Grey when her mother asks her to look into the disappearance of her neighbor Bo Shank, the former lead singer for a band Odelia idolized in her youth. But when a body is found in Bo Shank's house, everything quickly gets thrown out of tune.